PENGEMBANGAN POTENSI PEREKONOMIAN MELALUI ANALISIS SEKTOR EKONOMI UNGGULAN DI KABUPATEN MEMPAWAH - B21110034, GUSTA SURYA ABDIRATROMO (Jurnal Pembangunan dan Pemerataan, 2015)
The title of this study is to Economic Development Potential Through The Analysis Of Leading Economic Sector In Mempawah District. The purpose is to identify the leading economic sector in Mempawah district as the information and consideration to develop the economic potential in development planning. This study used secondary data, time series from Gross Regional Domestic Product (PDRB) in Mempawah district and West Kalimantan Province in 2009-2013. Data were analyzed by using analysis instruments, namely Location Quotient (LQ), Typologi Klassen, Shift Share. The result of Location Quotient analysis shows that agricultural sector, electricity, water supply and gaseous sector, and services sector are basic sectors in Mempawah district. The result of Tipologi Klassen analysis indicates that electricity, gaseous and water supply sector are devanced and rapidly growing sectors. Meanwhile the result of Shift Share analysis reveals that sector of mining and excavation, electricity, gaseous and water supply sectors are competitive sectors. The result of the analysis of each sector based on the three analysis instruments indicates that the leading sector in Mempawah district with the criteria basic sector, advance and rapidly growing sector, and competitive sector is sector of electricity, gaseous and water supply. Keywords: Leading Economic Sectors, Location Quotient, Typologi Klassen and Shift Share.